2016
DOI: 10.1186/s12944-016-0343-z
|View full text |Cite
|
Sign up to set email alerts
|

The APOA5 rs662799 polymorphism is associated with dyslipidemia and the severity of coronary heart disease in Chinese women

Abstract: BackgroundThe APOA5 rs662799 polymorphism has been widely reported regarding its associations with the plasma lipid levels and the occurrence of coronary heart disease (CHD), whereas its relationship with the severity of CHD has not yet been explored.MethodsFour hundred and seventy-eight angiografically defined subjects (325 CHD patients and 153 CHD-free controls) were enrolled in this study. The rs662799 polymorphism was genotyped, and the fasting lipid data were collected for all participants. The severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…ApoA5 also inhibits production of very low-density lipoprotein (VLDL) TG [ 5 6 7 ] and stimulates hydrolysis of VLDL TG mediated by lipoprotein lipase (LPL) [ 6 7 ], thereby reducing circulating TG levels [ 5 8 ]. Consequently, single-nucleotide polymorphisms (SNPs) in APOA5 have been shown to be involved in TG metabolism in both fasting and postprandial states and are considered as important contributors to the development of obesity, dyslipidemia, CVD, diabetes, and vascular complications in type 2 diabetes [ 9 10 11 12 13 ]. Among commonly studied APOA5 SNPs, -1131T > C (rs662799) and 56C > G (rs3135506) are considered to be functional-tag SNPs at APOA5 [ 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ApoA5 also inhibits production of very low-density lipoprotein (VLDL) TG [ 5 6 7 ] and stimulates hydrolysis of VLDL TG mediated by lipoprotein lipase (LPL) [ 6 7 ], thereby reducing circulating TG levels [ 5 8 ]. Consequently, single-nucleotide polymorphisms (SNPs) in APOA5 have been shown to be involved in TG metabolism in both fasting and postprandial states and are considered as important contributors to the development of obesity, dyslipidemia, CVD, diabetes, and vascular complications in type 2 diabetes [ 9 10 11 12 13 ]. Among commonly studied APOA5 SNPs, -1131T > C (rs662799) and 56C > G (rs3135506) are considered to be functional-tag SNPs at APOA5 [ 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among commonly studied APOA5 SNPs, -1131T > C (rs662799) and 56C > G (rs3135506) are considered to be functional-tag SNPs at APOA5 [ 12 13 ]. It has been previously reported that the frequency of the APOA5 -1131C allele is higher in East Asians (> 25%) than in Westerners (9–16%) [ 9 10 11 12 13 ]. The minor C allele of APOA5 rs662799 is associated with a higher circulating TG level and independently contributes to increased risk of CVD [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apolipoprotein A5 is the protein that is encoded by the APOA5 gene. It plays an important role in regulating the level of triglycerides in blood plasma [27]. The gene polymorphisms are associated with a change in the triglyceride level.…”
Section: Genes Responsible For the Digestion And Absorption Of Carbohmentioning
confidence: 99%
“…[11][12][13][14][15] Over the years, several common single nucleotide polymorphisms (SNPs) with significant effects on plasma TG levels have been identified, including genetic variants in lipoprotein lipase (LPL) and apolipoprotein A-V (APOA5). [16][17][18] Subsequently, genome-wide association studies (GWAS) were able to replicate these findings and identify additional loci, such as those encoding for tribbles pseudokinase 1(TRIB1), glucokinase regulator (GCKR), and angiopoietin-like protein 4 (ANGPTL4), thereby stressing the polygenic nature of plasma TG levels. 4,[19][20][21][22][23][24][25][26][27][28] It has been shown that loss of function variants in APOC3 results in decreased risk for CHD as shown in 2 large population cohorts.…”
Section: Introductionmentioning
confidence: 99%